Citarum Watershed Restoration through Community Involvement and Tourism Village Development - Novianti, Evi; Sjuchro, Dian Wardiana; Oktavia, Dina; Adnani, Qorinah Estiningtyas Sakilah; Gumilang, Lani; Sunardi; Nurfauziah, Isni (Jurnal Komunikasi, 2023)
The Citarum watershed is a source of livelihood for communities in 13 cities and regencies in West Java and Jakarta. However, the Citarum River is considered one of the most polluted rivers in the world, prompting the central and local governments to implement conservation programs. For Tarumajaya Village, the conservation of the Citarum watershed starts from the Situ Cisanti area accompanied by the development of a tourism village to support the Citarum Harum Program. However, the existing participation is only seen from the government side, and there is no significant community participation in terms of communication and others directly in the process of developing this tourism village. Thus, this study aims to identify community involvement in the development of tourism villages to support the restoration of the Citarum watershed in the Upper Citarum Region. This qualitative study was conducted in Tarumajaya Village, Kertasari Sub-district, Bandung Regency. Primary data were obtained through non-participant observation and in-depth interviews, while secondary data were obtained from policy documents. Data analysis included data reduction, presentation, verification, and conclusion drawing. The research findings show that the development of creative tourism villages in Tarumajaya Village is carried out to support environmental preservation and has economic value for the welfare of the community, thus supporting public health. Tarumajaya Village community innovation products have economic value in tourism and show community involvement in supporting sustainable tourism development which is expected to improve public health.